Prediction and laboratory diagnostics of hypertensive disorders in pregnancy - Balushkina A.A; Tyutyunnik V.L; Kan N.E; Harchenko D.K; Boris D.A (LCC «Medicine-Inform», 2019)
Prediction and laboratory diagnostics of hypertensive disorders in pregnancy A.A. Balushkina, V.L. Tyutyunnik, N.E. Kan, D.K. Harchenko, D.A. Boris Acad. V.I. Kulakov National Medical Research Center for Obstetrics, Gynecology, and Perinatology, Moscow, Russian Federation The major goal of perinatal care is to reduce maternal and perinatal morbidity and mortality. Hypertensive disorders which occurs in 10% (in Russia, in 5% to 30%) contribute greatly to the maternal morbidity and mortality. Every year more than 50,000 pregnant women die of the complications of hypertension. In developed countries, these complications rank second among the causes of antenatal and postnatal pathology being responsible for 20% to 25% of perinatal deaths. Hypertensive disorders remain a vital issue in present-day public health. Gestational hypertension, chronic hypertension, and preeclampsia have an important role in routine obstetrics determining maternal mortality and morbidity rates worldwide. Preeclampsia is one of the most common disorders in pregnancy accompanied by local intrauterine and systemic disturbances which result in significant maternal and fetal problems. Studies on the prediction and diagnosis of severe hypertension in pregnancy to determine management strategy, terms and method of birth are of crucial importance. Keywords: hypertensive disorders, gestational hypertension, chronic hypertension, preeclampsia, pregnancy, diagnostics, laboratory tests. For citation: Balushkina A.A., Tyutyunnik V.L., Kan N.E. et al. Prediction and laboratory diagnostics of hypertensive disorders in pregnancy. Russian Journal of Woman and Child Health. 2019;2(2):89-94.